Islamic Architecture between Civilizational Constants and External Influences: An Analytical Study of Environmental, Social, and Historical Dimensions - Tribak, Mohamed; Klaina, Mekki (International Journal of Education, Culture, and Society, 2025)
This study explores Islamic architecture as a holistic civilizational product shaped by the intricate interplay of religious, social, political, economic, and environmental factors. Rather than being a mere stylistic or aesthetic tradition, Islamic architecture is positioned as a dynamic expression of the Muslim Ummah’s identity and its contextual interactions. The research aims to analyze how these diverse factors have contributed to the development of a distinct architectural language and to evaluate the extent of influence from earlier civilizations, such as the Roman and Byzantine without compromising core Islamic values. The central research question investigates whether Islamic architecture can authentically represent Muslim identity and serve as a viable foundation for contemporary architectural practice. Employing an analytical and critical methodology, the study examines various architectural models within their historical and cultural contexts. The findings reveal that Islamic architecture reflects a balanced civilizational consciousness, integrating functionality with aesthetic and spiritual values. Moreover, it presents environmentally responsive and ethically grounded alternatives that can inform and enrich modern architectural development.